2001
DOI: 10.1089/153056201300093976
|View full text |Cite
|
Sign up to set email alerts
|

Use of Internet Technologies for Data Acquisition in Large Clinical Trials

Abstract: Data acquisition for automated processing is a central aspect of clinical trials with large numbers of cases because of their extensive demand for manpower. Scientific data can be collected using data forms, which are created in Hypertext Markup Language and published on the Internet. The completed data form can be returned via E-mail or Common Gateway Interface-Script and forwarded into a study database. For the Internet-based data acquisition of a prospective multicenter trial (e.g., on endophthalmitis incid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
16
1
1

Year Published

2003
2003
2013
2013

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 7 publications
0
16
1
1
Order By: Relevance
“…We believe this represents the first published experience at using PDAs to collect research data in the emergency department setting. Our results are somewhat less positive than other studies that have reported the use of hand-held computers to maintain clinical databases [8,9]. However, Lu and colleagues previously recognized similar barriers to physician use of PDAs [10].…”
Section: Discussioncontrasting
confidence: 61%
“…We believe this represents the first published experience at using PDAs to collect research data in the emergency department setting. Our results are somewhat less positive than other studies that have reported the use of hand-held computers to maintain clinical databases [8,9]. However, Lu and colleagues previously recognized similar barriers to physician use of PDAs [10].…”
Section: Discussioncontrasting
confidence: 61%
“…Our surveillance data comprised 370 treatment-years. We used a systematic online survey because this reporting system presents a unique tool in clinical research for acquiring data in a cost-and time-saving way with the advantage of automated data validation and standardization [28,29]. The participating centers were obligated to include all IBD patients ever treated with 6-TG, independently of whether the patients were still receiving treatment or not at time of data collection.…”
Section: Discussionmentioning
confidence: 99%
“…Based on the distribution and education heterogeneity of the professionals of the health area on the different regions of the country, the broad extension of the Brazilian territory, the irregular distribution of doctors and specialists, as well as the diversity of the quality and availability of health services in the country, recent studies 5,14-16,20,27-28 have focused on the urgent need to develop in Brazil proposals that enable the utilization of Telemedicine in several areas of health.…”
Section: Introductionmentioning
confidence: 99%